Ricardo Palma inside the theater of Peruvian independence. Ideological aspects in Rodil (1851) - Vallejo Sameshima, Miguel Ángel (2019)
This paper contextualizes Rodil, the only known drama by Ricardo Palma that belongs to the theatre about the Peruvian independence and the aesthetic of the Peruvian romanticism. The aim is to interpreter the ideological aspects of the play through an analysis of the acts of speaking.